Acute Hypoglycemia Induces Painful Neuropathy and the Treatment of Coenzyme Q10. (28th December 2015) - Zhang, Yan Ping; Mei, Shanshan; Yang, Jinfeng; Rodriguez, Yiliam; Candiotti, Keith A.
Abstract : Diabetic neuropathic pain is reduced with tight glycemic control. However, strict control increases the risk of hypoglycemic episodes, which are themselves linked to painful neuropathy. This study explored the effects of hypoglycemia-related painful neuropathy. Pretreatment with coenzyme Q10 (CoQ10) was performed to explore the preventive effect of CoQ10 on hypoglycemia-related acute neuropathic pain. Two strains of mice were used and 1 unit/kg of insulin was given to induce hypoglycemia. Mechanical sensitivity of hindpaw withdrawal thresholds was measured using von Frey filaments. Blood glucose levels were clamped at normal levels by joint insulin and glucose injection to test whether insulin itself induced hypersensitivity. Results suggest that the increased mechanical sensitivity after insulin injection is related to decreased blood glucose levels. When blood glucose levels remained at a normal level by the linked administration of insulin and glucose, mice demonstrated no significant change in mechanical sensitivity. Pretreatment with CoQ10 prevented neuropathic pain and the expression of the stress factor c-Fos. These results support the concept that pain in the diabetic scenario can be the result of hypoglycemia and not insulin itself. Additionally, pretreatment with CoQ10 may be a potent preventive method for the development of neuropathic pain.